THE EFFECT OF SERVICE QUALITY ON CUSTOMER SATISFACTION ON CV BAHAGIA SAMARINDA: PENGARUH KUALITAS PELAYANAN JASA TERHADAP KEPUASAN KONSUMEN PADA CV BAHAGIA SAMARINDA - Sattar Sattar; Mihani Mihani; Devi Sri Wahyuni (Indonesian Journal of Economy, Business, Entrepreneurship and Finance, 2021)
This study aims to analyze the effect of service quality on customer satisfaction at CV Bahagia Samarinda. This study uses five independent variables: tangible, reliability, responsiveness, assurance, and empathy, with one dependent variable, is customer satisfaction. After reviewing the literature and the field and formulating hypotheses, the data in this study were collected through distributing questionnaires to 50 people who had used the services of CV Bahagia Samarinda as the research sample. The sampling technique used is non-probability sampling. The data analysis method used is quantitative analysis, namely validity and reliability tests, simple linear regression, partial test (t) Coefficient of Determination Test (R2). Tangible does not have a significant effect on customer satisfaction with the services of CV Bahagia Samarinda. This can be seen from the t-test results on concrete variables with a calculated t value of 0.885, which is smaller than the t table value with a value of 1.99 and a significant value of 0.381 greater than 0.05 ( 0.381 > 0.05 ), so H1 is rejected. Does not have a significant effect on customer satisfaction with the services of CV Bahagia Samarinda. This can be seen from the results of the t-test on the Reliability variable 1.280, which is smaller than the t table value with a value of 1.99 and a significant value of 0.207 greater than 0.05 (0.207 > 0.05), so H2 is rejected. Responsiveness has no significant effect on customer satisfaction at CV Bahagia Samarinda services. This can be seen from the results of the t-test on the Responsiveness variable 1.529, which is smaller than the t table value with a value of 1.99 and a significant value of 0.134, which is greater than 0.05 (0.134 > 0.05), so H3 is rejected. Assurance has a significant effect on customer satisfaction with the services of CV Bahagia Samarinda. This can be seen from the results of the t-test on the Assurance variable 3.305, which is greater than the t table value with a value of 1.99 and a significant value of 0.002 less than 0.05 (0.002 < 0.05), so H4 is accepted. Empathy has no significant effect on customer satisfaction at CV Bahagia Samarinda's services. This can be seen from the results of the t-test on the Empathy variable 1.429, which is smaller than the t table value with a value of 1.99 and a significant value of 0.160, which is greater than 0.05 (0.160 > 0.05), so H5 is rejected. Tangible, Reliability, Responsiveness, Assurance, and Empathy have a simultaneous effect on customer satisfaction at CV Bahagia Samarinda services. The statistical value evidences this with a significant value of 0.002. Therefore, the significant value is less than 0.05 (0.002 < 0.05). Therefore, simultaneously service quality has a significant effect on customer satisfaction